2019
DOI: 10.1021/acssuschemeng.9b02232
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Pure Ionic Liquids and Their Complex Fluids: A Review

Abstract: Ionic liquids (ILs) are liquid salts at ambient or lower temperatures and consist of ions and short-lived ion pairs. They are potential alternatives to toxic, hazardous, highly flammable, and volatile solvents for preparing solutions, dispersions, gels, composites, and polymeric melts. ILs have some very interesting and unique characteristics like good chemical and thermal stability and very low vapor pressures. They have good solvation interactions with a wide range of organic, inorganic, and polymeric compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 259 publications
(399 reference statements)
1
59
0
Order By: Relevance
“…Mud samples having higher organic matter content (RVand RT) had a higher complex modulus (417 Pa and 7909 Pa) than the ones with lower organic matter content (13 Pa and 1774 Pa), for a given density. The complex modulus is a measure of the consistency of the system, while the phase angle is representative of the degree of structuration (Lupi et al 2016;Shakeel et al 2018;Shakeel et al 2019b;Shakeel et al 2019c). The results showed that the consistency of the mud samples can be varied by changing the OM content or density, whereas the degree of structuration remains the same for all the samples.…”
Section: Methodsmentioning
confidence: 98%
“…Mud samples having higher organic matter content (RVand RT) had a higher complex modulus (417 Pa and 7909 Pa) than the ones with lower organic matter content (13 Pa and 1774 Pa), for a given density. The complex modulus is a measure of the consistency of the system, while the phase angle is representative of the degree of structuration (Lupi et al 2016;Shakeel et al 2018;Shakeel et al 2019b;Shakeel et al 2019c). The results showed that the consistency of the mud samples can be varied by changing the OM content or density, whereas the degree of structuration remains the same for all the samples.…”
Section: Methodsmentioning
confidence: 98%
“…Note that the high viscosity of cellulose-IL solution adversely affects heat-and mass transfer; the problem is compounded if the solution shows Newtonian behavior, i.e., no shear-thinning is produced by increasing solution shear (agitation) [29]. Consequently, studying rheological properties such as viscoelasticity and flow behavior of cellulose solutions is important [30,31]. These properties are relevant because they allow process optimization, or reveal functional properties for A recent publication showed that cellulose thermal stability in BuMeImCl (24 h at 130 • C) is enhanced by co-solubilization of several amino acids, L-arginine being the most effective stabilizer.…”
Section: Ionic Liquids Quaternary Ammonium Electrolytes and Salts Omentioning
confidence: 99%
“…The micrograph of the prepared system shows the existence of a structured network along with the nanoparticle-stabilized droplets (Figure 1c), which verified the dual stabilization of the system. Apart from microscopic analysis, rheological investigation was also carried out for the prepared systems, which is a useful tool to analyse the structure-property relationship in different systems [19]. Frequency sweep tests were performed, within the linear viscoelastic regime, for the samples to investigate their mechanical properties without disturbing the structure.…”
Section: Resultsmentioning
confidence: 99%